Metaphorically Speaking: Pre-Service EFL Teachers' Understanding and Conceptions of (Teacher) Research - Savasci, M.; Atar, Cihat (JOURNAL LANGUAGE TEACHING & LEARNING, 2024)
Given the scarcity of research focusing on pre-service teachers' research engagement, this paper embarks on a qualitative descriptive study about how a group of Turkish English-as-a-foreign-language (EFL) pre-service teachers (PSTs) understand and conceptualize teacher research. Notably, this study addresses a significant gap in the existing literature, for it explores this issue using metaphor analysis, a method that has not been previously employed. Considering the potency of the use of metaphor analysis in revealing underlying beliefs, this study attempts to explore PSTs' perceived conceptions of reading and conducting research on their future engagement in and with teacher research through conceptual metaphors. The participants were Turkish EFL PSTs (N= 41) who had previously completed an undergraduate research methodology course and carried out small-scale research projects prior to data collection. Data were triangulated via three instruments: A survey, a metaphor completion task, and interviews. Research and teacher research metaphors were elicited via two metaphor prompts, namely Research is like...because... and Teacher research is like...because.... Responses to closed -ended survey questions were analyzed by descriptive statistics whilst data coming from open-ended survey questions and interviews underwent inductive content analysis. Additionally, the metaphorical conceptions were analyzed by metaphor analysis. Findings illustrated that although PSTs considered research engagement valuable in terms of improving their pedagogical and content knowledge, they did not appear to focus much on personal or intellectual gains. Hence, these findings provide insights into how PSTs conceptualize teacher research following their exposure to research experiences. The implications are discussed focusing on providing implications for pre-service teacher training, and suggestions are made for further research in this field. (c) Association of Applied Linguistics. All rights reserved
Keywords: Pre-service teachers; Teacher research; Action research; Research engagement; Metaphor; Pre-service EFL teachers; Education & Educational Research